Management of Severe Colitis and Toxic Megacolon - Liggett, Marjorie R.; Alam, Hasan B. (Clinics in Colon and Rectal Surgery, 2023)
Severe colitis is a well-defined condition encompassing several etiologies but is most often caused by severe ulcerative colitis or Clostridioides difficile infection. Severe colitis can evolve into toxic colitis, or toxic megacolon when associated with bowel dilation and systemic manifestations, resulting in a life-threatening scenario where multidisciplinary management is often required. Medical management continues to play an important role in the initial treatment of toxic megacolon. However, timely surgical intervention can be lifesaving.
Keywords: toxic colitis; toxic megacolon; subtotal abdominal colectomy with end ileostomy